2010
DOI: 10.1002/csr.223
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable entrepreneurship in SMEs: a case study analysis

Abstract: Sustainability is oft thought of as the privilege of the large corporate -with suffi cient funds to invest in anything from effective green Public Relations (PR) to improving its carbon footprint. What is perhaps less well-understood and documented is the range of activities undertaken by small and medium enterprises (SMEs), including very small entrepreneurial start-ups, some of which base their entire business rationale on sustainable principles. This paper uses a case study approach to explore the modus ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 7 publications
5
87
1
5
Order By: Relevance
“…However, in this regard, there is no consensus among academics. While Rodgers [95] found that firms with SEO have a risk tolerance over any other entrepreneurial firm, Spence et al [53] and Gawel [1] indicate that risk taking exists but is calculated and limited, and Lumpkin et al [41] argue that, in this type of firm, risks tend to be avoided. In any case, as stressed by Murillo-Luna et al [136], a proactive strategy towards sustainable development involves the implementation of new processes, technologies and systems, and this always carries a certain risk due to the uncertainty of its eventual impact on organizational performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this regard, there is no consensus among academics. While Rodgers [95] found that firms with SEO have a risk tolerance over any other entrepreneurial firm, Spence et al [53] and Gawel [1] indicate that risk taking exists but is calculated and limited, and Lumpkin et al [41] argue that, in this type of firm, risks tend to be avoided. In any case, as stressed by Murillo-Luna et al [136], a proactive strategy towards sustainable development involves the implementation of new processes, technologies and systems, and this always carries a certain risk due to the uncertainty of its eventual impact on organizational performance.…”
Section: Discussionmentioning
confidence: 99%
“…Corporate social responsibility [46] Corporate sustainable entrepreneurship [2,10] Ecopreneurship [30,95] Environmental corporate entrepreneurship [96] Environmental entrepreneurship [22,59] Enviropreneurial marketing [34] Enviropreneurship [96] Green entrepreneurship [22] Macro-entrepreneurship [97] Social entrepreneurship [22] Sustainability entrepreneur [47] Sustainable development innovation [98] Sustainable entrepreneurship [10,25,47,90,99] Sustainable intrapreneurship [100] Sustainopreneurship [47] All these terms have in common a unique, holistic view of the business context, conceived with a long-term horizon and a commitment to responding to current and future stakeholders [60,62,88,101] according to SEO fundamentals. In this sense, sustainably-and entrepreneurially-oriented firms actively contribute-together with other organizations, institutions and public and private associations from economic, social and political circles-to sustainable development [102] as stated in the Brundtland Report [4].…”
Section: Termsmentioning
confidence: 99%
“…Environmental awareness and action is insufficient [24], entrepreneurs usually ignore their business environmental impact since by definition SMEs have limited resources, while tackling environmental issues put an additional strain on them, and are unwilling or unable to act due to time and resource constraints [22]. This, however, does not mean that all SMEs ignore sustainability [25], since there is evidence of SMEs aligned with ecological paradigms [26], especially small and young SMEs [27].…”
Section: Sustainable Entrepreneurshipmentioning
confidence: 99%
“…Significant conceptual problems persist, mainly due to concept Sustainability 2017, 9, 1779 3 of 36 novelty and multidimensionality, which has to be considered [15,16,25,29,30]. The relationship between entrepreneurship and environment have been examined by various scholars and addressed by different concepts [18,27] such as sustainability entrepreneurship [31], sustainable entrepreneurship [6,8,[32][33][34], environmental entrepreneurship [10,20,35], ecopreneurship and green management [25,29,30,36] or green entrepreneurship [37] which, broadly, relates roughly to the same concept. As a consequence, various scholars assert that entrepreneurs had to play an active role in balancing economic and ecological goals [6].…”
Section: Sustainable Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation